Contribution of Chitinases to Listeria monocytogenes Pathogenesis - Chaudhuri, Swarnava (American Society for Microbiology (ASM), 2010)
Listeria monocytogenes secretes two chitinases and one chitin binding protein. Mutants lacking chiA, chiB, or lmo2467 exhibited normal growth in cultured cells but were defective for growth in the livers and spleens of mice. Mammals lack chitin; thus, L. monocytogenes may have adapted chitinases to recognize alternative substrates to enhance pathogenesis.